Problem-Based Learning-Collaboration (PBL-C) Model in Elementary School Science Learning in the Industrial Revolution Era 4.0 and Indonesia Society 5.0 - Sajidan, S.; Suranto, S.; Atmojo, I. R. W.; Saputri, D. Y.; Etviana, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This study aims to describe the problem-based learning and collaboration model on science learning in elementary schools in the Industrial Revolution era 4.0 and Indonesia Society 5.0. This research is qualitative and descriptive. Data collection activities at the preliminary stage are carried out by exploring elementary school teachers' perceptions of problem-based learning and its application in science learning in schools in Surakarta, Indonesia. Focus group discussions (FGD) were conducted on 20 elementary school teachers employing the open inquiry method. The discussion reviewed several topics related to the teachers’ perception of the problem-based learning application, the advantages and disadvantages of problem-based learning as the basis for modifying the learning model, and the importance of collaboration skills for elementary school students. The problem-based learning-collaboration (PBL-C) model is a development of the problem-based learning model, which is equipped with collaborative skill indicators from the Industrial Revolution 4.0 aspects and coordination indicators with various parties from Indonesia Society 5.0 aspects. The result of this research is the problem-based learning-collaboration (PBL-C) model design with six steps: (1) orientation of students to problems, (2) organizing students for learning and division of tasks, (3) guiding investigations on local community leaders, (4) proving the results of the investigation, (5) developing and presenting the work, and (6) analyzing and evaluating the problem-solving process.